Optimal RoadSide Units Distribution Approach in Vehicular Ad hoc Network - Ali Kies; Khedidja Belbachir; Zoulikha Mekkakia Maaza; Claude Duvallet (IAES Indonesian Section, 2022)
A vehicular ad hoc network is a particular type of ad hoc mobile network. It is characterized by high mobility and frequent disconnection between vehicles. For this, the roadside units (RSUs) deployment permits to enhance the network connectivity. The objective of this work is to provide an optimized RSUs placement for enhancing the network connectivity and maximizing the accident coverage with reducing the deployment cost. In this paper, we propose our approach called Optimized RoadSide units Deployment (ORSD). The proposed approach comprises a two-step, in the first step, ORSD finds the RSUs candidate locations based on network density and connectivity. We calculated the connectivity of each segment based on speed and arrival information’s. The second step permit to find the optimal solution of our proposed objective function. The objective function permits to enhance the network connectivity and maximizing the accident coverage. To find the optimal solution of our objective function is an NP-complete problem of order o(n²) . Therefore, we propose to solve this problem in two phases, so that it becomes a simple linear problem to solve. The ORSD is proposed for urban and high way scenarios. The extensive simulation study is conducted in order to assess the effectiveness of the proposed approach. We use the Simulator of Urban MObility (SUMO) for generating different traffic scenarios. We develop scripts to extract different information as density, speed and travel time in each segment. Then, we develop an algorithm to calculate connectivity probability for each segment. Then, we implement our objective function to finds optimal RSUs positions in terms of connectivity, accident cover and cost.